2016
DOI: 10.18632/oncotarget.7212
|View full text |Cite
|
Sign up to set email alerts
|

Regression/Eradication of gliomas in mice by a systemically-deliverable ATF5 dominant-negative peptide

Abstract: Malignant gliomas have poor prognosis and urgently require new therapies. Activating Transcription Factor 5 (ATF5) is highly expressed in gliomas, and interference with its expression/function precipitates targeted glioma cell apoptosis in vitro and in vivo. We designed a novel deliverable truncated-dominant-negative (d/n) form of ATF5 fused to a cell-penetrating domain (Pen-d/n-ATF5-RP) that can be intraperitoneally/subcutaneously administered to mice harboring malignant gliomas generated; (1) by PDGF-B/sh-p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 42 publications
(57 reference statements)
0
49
0
Order By: Relevance
“…A dominant/negative-sequence follows in which the DNA binding domain of ATF5 is substituted by an amphipathic sequence with a leucine repeat at every seventh residue and then by the human ATF5 basic leucine zipper (bZIP) domain truncated after the first valine (26-29). Parallel work has demonstrated that a similar recombinant tagged peptide passes the blood brain barrier, enters intact cells both in vivo and in vitro and promotes selective death of glioma cells (19). Four independent batches of the peptide (including one under GMP conditions) have had comparable activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A dominant/negative-sequence follows in which the DNA binding domain of ATF5 is substituted by an amphipathic sequence with a leucine repeat at every seventh residue and then by the human ATF5 basic leucine zipper (bZIP) domain truncated after the first valine (26-29). Parallel work has demonstrated that a similar recombinant tagged peptide passes the blood brain barrier, enters intact cells both in vivo and in vitro and promotes selective death of glioma cells (19). Four independent batches of the peptide (including one under GMP conditions) have had comparable activity.…”
Section: Resultsmentioning
confidence: 99%
“…To provide a potential means to target ATF5 in vivo , we designed a d/n-ATF5 linked to a cell penetrating domain (Penetratin) (19). This recombinant peptide passes the blood brain barrier, enters tumor cells and exerts antineoplastic activity in a rodent transgenic glioma model.…”
Section: Introductionmentioning
confidence: 99%
“…The delivery of Cx43 activity targeting compounds to brain tumors pose important challenges that will need to be overcome to realize this potential. Interestingly, cell penetration sequences similar to those incorporated in a number of the peptides listed in Table 1 have shown facility for crossing the blood brain barrier [51,66]. Use of drug delivery vehicles including exosomal vectors may also assist in this key task [67].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…This fusion was manufactured in bacteria as Cell Penetrating-d/n-ATF5 recombinant peptide (CP-d/n-ATF5-RP), or as a chemically synthesized peptide (CP-d/n-ATF5-S1). Both forms included truncation of 25 C-terminal amino acids, and exclusion of the C-terminus domain, to reduce aggregation without compromising efficacy (Figure 1C & D) [12]. I n vitro , CP-d/n-ATF5-RP and CP-d/n-ATF5-S1 promoted apoptosis of cancer cell lines.…”
Section: Forummentioning
confidence: 99%
“…I n vitro , CP-d/n-ATF5-RP and CP-d/n-ATF5-S1 promoted apoptosis of cancer cell lines. In fact, CP-d/n-ATF5-S1 was shown to promote apoptosis in a broad spectrum of tumors (Table 1) [5, 12]. CP-d/n-ATF5-S1 induces apoptosis by disrupting the expression of prosurvival proteins, ATF5 itself, deubiquitinase USP9X, BCL2, BAG3, and MCL1 [5].…”
Section: Forummentioning
confidence: 99%